2007
DOI: 10.1002/cae.20092
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of student performance in traditional mode and online mode of learning

Abstract: There has been interest for many decades in comparing the effectiveness of technology-delivered instruction with traditional face-to-face teaching and measurable student outcomes have been an important indicator. Having pointed to salient aspects of the current academic environment and to some of the key literature in this area, this article analyses the performance of two groups of students studying in the traditional mode and the online mode in a masters program delivered by a Department of Computing at a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 1 publication
1
10
0
3
Order By: Relevance
“…On the other hand, there are almost 50% (n2=30) of students in the blended class who gained the highest grade (M2=8.03). The study revealed that there was a highly significant difference in academic achievement of students between conventional learning class and blended learning class (p<0.01) as conceived in [10], who found that traditional-mode students have achieved a slightly better performance in examinations in comparison with online-mode students.…”
Section: A Students' Preferences For Learning Modelmentioning
confidence: 92%
“…On the other hand, there are almost 50% (n2=30) of students in the blended class who gained the highest grade (M2=8.03). The study revealed that there was a highly significant difference in academic achievement of students between conventional learning class and blended learning class (p<0.01) as conceived in [10], who found that traditional-mode students have achieved a slightly better performance in examinations in comparison with online-mode students.…”
Section: A Students' Preferences For Learning Modelmentioning
confidence: 92%
“…The major forces driving its popularity are (1) the emergence of a worldwide communication network, with powerful computer technologies leading to a revolution in all sectors, including education; (2) the perception of e-learning as a solution to the cost and quality problems of universities (Selim, 2007); and (3) profound changes in the ways in which we work and live, which are necessitating a new concept of education for those who have irregular working schedules and both family and employment commitments (Marks, Sibley, & Arbaugh, 2005;Shen, Chung, Challlis, & Cheung, 2007). University students are becoming more diverse and the demand for e-learning courses is going up (Papp, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As Shen, Chung, Challis, and Cheung [2] point out, researchers have been interested in comparing alternative forms of instructional delivery at least since the 1970s when print, audio, and video means were used to bring education to remote students. For a time, the "no significant difference phenomenon" described by Thomas Russell [7] was used to support the notion that technology-driven instruction was as effective as classroom-driven instruction.…”
Section: Existing Researchmentioning
confidence: 99%